Gamificación en el desarrollo de habilidades comunicativas del quinto grado “B”, sección vespertina, de la Escuela “Miguel Riofrío”, ciudad de Loja, 2021-2022. - Rojas Bejarano, Marjorie Teresa (2022)
Gamification in the educational field is a strategy used by teachers in order for the child to play while they are in a learning process; In this space, it is necessary to consider the communication skills that students use to function assertively in playful processes.The general objective of this research is to contribute to the development of communication skills through gamification; For its fulfillment, the following specific objectives have been proposed: diagnose the communication skills that fifth grade students have, propose a proposal for the development of communication skills through gamification and, finally, execute and evaluate the proposal using gamification for development. of communication skills. The research supports a mixed, qualitative and quantitative approach; it is of descriptive type allowing an approach to the educational reality; and, with a cross-sectional design because the data collection was developed at a certain time, likewise, the methods were used: synthetic, analytical, deductive, inductive and statistical; To obtain the information, a survey was applied to the teachers and an observation sheet to the students before and after executing the didactic proposal. The investigated sample consists of three teachers and twenty-three students of the fifth grade "B" of the Miguel Riofrío educational institution. The results obtained allow us to show that gamification allows the development of communication skills, since, after executing the proposal with gamified activities for two weeks, in a period of 2 daily periods, it is found that the improvement is 46%. Therefore, the teacher must create spaces for active participation that allow students to develop communication skills through the interaction that the game fosters. Keywords: gamification, communication skills, educational games, active learning.